A Systematic Literature Review of Factors Caused Academic Fraud Behavior - Dwi Suhartini; Hero Priono; Astrini Aning Widoretno; Galuh Tiaramurti (Future Science)
This study uses the literature review method because it aims to analyze the factors that cause academic fraud behavior by looking at the fraud theory used and the research method approach. The factors examined include the theory of the pentagon dimension proposed by Jonathan Marks in 2012 and the GONE theory coined by Jack Bologna in 1992. Pentagon theory has five factors namely pressure, opportunity, rationalization, ability, and arrogance. While the GONE theory is four factors, namely Greed, Opportunity, Need, and Expose. In this study, several journals have been examined related to the theory of the pentagon dimension and the GONE theory so that it can be concluded that there is pressure because students want high grades and the desire to graduate immediately. Besides, the opportunity students have, to do academic cheating and rationalization that making the idea that fraud academic behavior is common. Those three factors are most influential in academic fraud behavior. With this conclusion, it can be suggested to lecturers to optimize learning methods that combine hard skills and soft skills to prevent academic fraud behavior to happen.